Analysis of Product Quality Control Using Statistical Process Control (SPC) at Didik Bag Convection in Bandung - Nadiya Yusriyyah; Camelia Rizki Agrina (Master Manajemen, 2025)
Didik Bag Convection is a manufacturing business specializing in bag production. However, its production activities often encounter issues related to product quality, such as defects caused by employees' lack of understanding of new sewing machines, the absence of standard operating procedures (SOPs), and an unsupportive work environment. To address these issues, quality control measures are necessary, which can be analyzed using Statistical Process Control (SPC) to identify the root causes of defects in product quality and production processes. The quality control analysis techniques employed include Check Sheets, Pareto Diagrams, Control Charts (P-Charts), and Fishbone Diagrams (Cause-and-Effect Diagrams). The results of this study indicate that the quality control at Didik Bag Convection is within acceptable limits as it falls within normal control boundaries. The number of defective products remains within a reasonable threshold. Based on the Pareto Diagram, damaged stitching defects account for the highest proportion of defects, making up 43.28% of the total defects. Improvements to address stitching defects are needed, which can be achieved using the Fishbone Diagram by focusing on the factors of Man (human resources), Material (raw materials), Machine, Method, and Environmental indicators that influence product defects during production.